PROSPECTS FOR DEVELOPMENT OF GEOLOGICAL MONUMENTS OF KRYVYI RIG FOR SCIENTIFIC, EDUCATIONAL AND TOURISM ACTIVITIES - Kurylo, M.; Bondar, Y. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It’s defined geological objects with favorable conditions of following preservation and developing. There are granitoids of Lozuvatka village, quartzites of Lativka village, amphibolites of Rakhmanovo village, outcrop of Skeliuvatka Suite of Paleo-Proterozoic Kryvyi Rih Series, "Sceli MODRu", Вalka Pivnichna Chervona, Karachunivski granites, Kirov historical and geological monument. It was developed excursion route on the geological monuments of Krivyi Rig. The method of determining the value of geological objects is proposed.